Modern approaches of effective prevention of NSAIDs-gastropathy - A. Ye. Karateyev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
The aim of review. To present current approach for NSAIDs-gastropathy prevention.Summary. Upper gastrointestinal lesions, related to intake of nonsteroid anti-inflammatory drugs (NSAIDs) represent a serious social and medical problem. This is related to increase in NSAIDs and low dozes of aspirin users number, who are mostly elderly people, often having combination of several diseases with serious risk of drug-induced complications. Even after safer class of NSAIDs, i.e. selective cyclooxygenase-2 (COX-2) inhibitors were introduced to clinical practice and obvious successes in treatment of H. pylori-associated peptic ulcers, frequency of NSAIDs gastropathy still remains high. Besides that, NSAIDs gastropathy complications, such as bleeding and perforations, are accompanied by high mortality and serious treatment expenditures. This requires adequate prophylaxis of this pathology. Proton pump inhibitors (PPIs) play a special role as the main class of drugs used for NSAIDs gastropathy prevention at the present time. This review presents advantages of pantoprazole — a PPI, that possesses the minimal risk of unfavorable pharmacological interaction with drugs of other pharmacological classes.Conclusion. Application of less aggressive NSAIDs — selective COX-2 inhibitors and H. pylori eradication reduce risk of serious complications, but does not eliminate it completely. Therefore long-term PPI application is required for prevention of NSAID-related ulcers and gastro-intestinal bleeding in patients who receive NSAIDs on regular basis, in the case if they have risk factors for NSAIDs-gastropathy.